2013
DOI: 10.21837/pm.v11i3.110
|View full text |Cite
|
Sign up to set email alerts
|

Commuters Perceptions on Rail Based Public Transport Services: A Case Study of KTM Komuter in Kuala Lumpur City, Malaysia

Abstract: In facing the challenges of urban traffic congestion, when people are becoming more dependent on private vehicles, public transportation services should be functioning effectively as attractive alternative modes. This research evaluates how rail public transport users perceive day to day quality of the provided services. The study investigates commuters‟ satisfaction levels of various trip making aspects on board KTM Komuter trains, a commuter services operated by the company Keretapi Tanah Melayu Berhad (KT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Among others, Yanık et al [24] and Yilmaz and Ari [25] studied the metro and high-speed rail service in Turkey, Shen et al [26] reported user satisfaction with the urban rail transit in China, and Lai and Chen [27] conducted a case study on the Kaohsiung Mass Transit (KMRT) in Taiwan. Researchers in Malaysia focused on user satisfaction with rail transit, primarily the commuter service [28][29][30] and light rail transit [6,31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Among others, Yanık et al [24] and Yilmaz and Ari [25] studied the metro and high-speed rail service in Turkey, Shen et al [26] reported user satisfaction with the urban rail transit in China, and Lai and Chen [27] conducted a case study on the Kaohsiung Mass Transit (KMRT) in Taiwan. Researchers in Malaysia focused on user satisfaction with rail transit, primarily the commuter service [28][29][30] and light rail transit [6,31,32].…”
Section: Introductionmentioning
confidence: 99%